Biocatalytic One-Carbon Transfer – A Review - Germer, Philipp; Andexer, Jennifer N.; Müller, Michael (Synthesis, 2022)
This review provides an overview of different C1 building blocks as substrates of enzymes, or part of their cofactors, and the resulting functionalized products. There is an emphasis on the broad range of possibilities of biocatalytic one-carbon extensions with C1 sources of different oxidation states. The identification of uncommon biosynthetic strategies, many of which might serve as templates for synthetic or biotechnological applications, towards one-carbon extensions is supported by recent genomic and metabolomic progress and hence we refer principally to literature spanning from 2014 to 2020.1 Introduction2 Methane, Methanol, and Methylamine3 Glycine4 Nitromethane5 SAM and SAM Ylide6 Other C1 Building Blocks7 Formaldehyde and Glyoxylate as Formaldehyde Equivalents8 Cyanide9 Formic Acid10 Formyl-CoA and Oxalyl-CoA11 Carbon Monoxide12 Carbon Dioxide13 Conclusions
Keywords: biosynthesis; methyl transfer; enzyme cascades; enzymes; C1 building blocks